Determining Subclinical Edema in Fuchs Endothelial Corneal Dystrophy: Revised Classification using Scheimpflug Tomography for Preoperative Assessment - Sun, Susan Y.; Wacker, Katrin; Baratz, Keith H.; Patel, Sanjay V. (Ophthalmology (Rochester, Minn.), 2019)
To determine if Scheimpflug tomography can identify subclinical corneal edema in Fuchs endothelial corneal dystrophy (FECD), and to recommend a new classification of FECD for clinical practice and research. Cross-sectional study with follow-up of outcomes. Ninety-three eyes from 57 subjects with a range of severity of FECD and 74 eyes from 40 subjects with normal corneas. Corneas were clinically assessed for FECD and corneal edema by using slit-lamp biomicroscopy, and categorized as having clinically definite edema (obvious visible edema), being suspicious for subclinical edema (possible corneal thickening without obvious edema on slit-lamp examination), or not having edema (no clinical suspicion of edema). Tomographic pachymetry and elevation maps derived from Scheimpflug images were evaluated by 3 masked observers for specific features believed to be consistent with corneal edema. FECD clinical disease course and outcomes were reviewed from the time of Scheimpflug image acquisition to the last available follow-up. Presence of tomographic features: (1) loss of parallel isopachs, (2) displacement of the thinnest point of the cornea, and (3) focal posterior corneal surface depression. Clinical outcomes included the change in central corneal thickness (CCT) and vision after endothelial keratoplasty (EK). The 3 specific tomographic features were all present in all FECD corneas with clinically definite edema (n = 15), in ≥81% of FECD corneas suspicious for subclinical edema (n = 16), in ≤42% of FECD corneas deemed not to have edema (n = 62), and in ≤5% of normal corneas (n = 74). Corneas suspicious for subclinical edema that subsequently underwent EK (n = 9) all had at least 2 of the tomographic features present before EK, and improvement in vision, CCT, and tomographic features after EK confirmed the presence of subclinical edema preoperatively. Subclinical corneal edema in FECD can be detected by Scheimpflug tomography. We recommend classifying FECD corneas as having clinically definite edema (based on slit-lamp examination), subclinical edema (based on tomographic features without clinically definite edema), or no edema (no tomographic or slit-lamp features of edema). This classification is independent of CCT and should be considered when evaluating FECD eyes for cataract surgery or EK.